EFFECT OF PRESSURE ON THE IONIC CONDUCTIVITY OF (AgI)0.7(AgPO3)0.3 GLASS - Mardiyanto Mardiyanto; E. Kartini; Gunawan Gunawan; A. Hindasyah; M. Ihsan (Jurnal Sains Materi Indonesia, 2007)
EFFECT OF PRESSURE ON THE IONIC CONDUCTIVITY OF (AgI)0.7(AgPO3)0.3 GLASS. Since the discovery of ionic conductivity in glass systems a few decades ago, the research and development on the ionic conductive superionic glass has become quite active. In particular, the proposed application of glass electrolytes to rechargeable batteries has strongly stimulated the research and development effort. A key issue is the understanding of the nature of the ionic transport mechanism. The ionic conductivity is a product of the charge carrier concentration and the charge carrier mobility, which, in glass electrolytes, is strongly associated with the mobility of the ionic carrier through the microscopic glass defect. In order to improve our understanding about the ionic conductivity the effect of pressure on the ionic conductivity of silver based electrolyte glass of (AgI)0.7(AgPO3)0.3 has been studied. From these experiments it is shown that the higher the pressure the larger the ionic conductivities are obtained. The powder electrolyte glasses were pressed into coin type samples with pressure of 100 kg/cm2, 200 kg/cm2, 300 kg/cm2, 700 kg/cm2 and their conductivities of 1.66 x 10-05 [S/cm], 1.01 x 10-04 [S/cm], 1.32 x 10-04 [S/cm], 1.63 x 10-04 [S/cm] were obtained when they were measured with LCR meter at 50 Hz. The change of the conductivities may be caused by the increase of the microscopic defects in the material due to the higher applied pressures. Densities of the coin type samples were also calculated. The results of the calculations were 3.950 g/cm3, 4.015 g/cm3 , 4.115 g/cm3 , 5.477 g/cm3 for the applied pressures of 100 kg/cm2, 200 kg/cm2, 300 kg/cm2, 700 kg/cm2 respectively.